Socioeconomic factors affecting trastuzumab usage in patients with breast cancer in a resource constrained setting in North India - Singh, Pragya; Pasricha, Rajesh; Pandey, Laxman; Joseph, Deepa; Ibrahim, Ajas; Bhadoria, Ajeet S.; Gupta, Manoj; Ravi, Bina (International Journal Of Community Medicine And Public Health, 2020)
Background: Trastuzumab is now the standard of care in patients with Her-2 positive breast cancer. Despite its availability, high cost of treatment of trastuzumab makes it out of reach for many patients. This study analyses access to trastuzumab and identified potential barriers to its use in a large tertiary care hospital in northern India. Methods: This is a cross- sectional study of all the Her-2 positive breast cancer patients diagnosed and treated in our institute in 2018. These patients were investigated to look into various socio-economic factors for acceptance or non-acceptance of trastuzumab by using a predesigned questionnaire. Chi square test or Fishers exact test was applied. Results: Out of 310 diagnosed cases of carcinoma breast 52 (16%) patients were Her-2 positive. The majority of the trastuzumab recipients belonged to upper/middle socioeconomic status as compared to the non-recipient group (75% vs. 34.4%, P=0.004). Most of the receiver were well-educated (75% vs. 28.2%, P= 0.0009) and belonged to the high-income strata (55% vs. 37.5%, P= 0.22). It was found that the treatment of maximum (84.6%) Her-2 positive patients were met by out- of- pocket expenditure (OOPE) and 71.9% of the patients cited financial issues as the main cause of not taking the drug. Conclusions: The patient’s socioeconomic class and their education level significantly influenced the usage of the drug. Improving patient education as well as the implementation of the government health scheme can improve the availability and usage of this drug.